The Effectiveness of Scrapbook as A Media to Improve Students’ Ability in Writing Recount Text “a Case of The Eighth Grade Students of SMP N 2 Gubug in the 2015 / 2016 Academic Year - M Wahyu Widiyanto; Ulfah Ulfah; Alfiana Zia (ETERNAL (English Teaching Journal), 2015)
The aims of this study are:1) To find out the students’ ability in writing recount text who were taught using scrapbook. 2) to find out the students’ ability in writing recount text who were taught without using scrapbook. 3) to know whether there is any significant difference of the students’ ability who were taught using Scrapbook and the students who were taught without using Scrapbook. This study used true experimental design and its kind is pre-test post-test control and experimental group design. The population in this research is the eighth grade students of SMP N 2 Gubug in the 2015/2016 academic year. The writer took 2 classes, each class consist of 21 students, VIII A as Control class and VIII B as Experimental class. Pre-test and post-test were used as instruments. There were some categories in assessing writing, those are: content, organization, vocabulary, syntax and mechanic. Based on the research findings, the writer concluded that the mean of students’ score in writing recount text taught without using Scrapbook is 65,6 and it was categorized as “adequate” in achievement level. So it was concluded that writing ability of the students who were taught without Scrapbook is fair. The mean of students’ score in writing recount text taught using Scrapbook is 74,57 and it was categorized as “good” in achievement level. So it was concluded that the use of Scrapbook can improve the students’ ability in writing recount text. There was significant improvement of students’ ability in writing recount text after being taught by using Scrapbook. It can be known from ttest result is 3,58 and ttable for df 40 and significance 5% is 2,021. From data above, because t-test is higher than t-table, so the null hypothesis (H0) was rejected, and Ha was accepted. So there is significant difference between the students’ ability in writing recount text taught using scrapbook and those were taught without using Scrapbook. Based on the result above, it can be concluded that the use of Scrapbook is effective in improving students’ ability in writing recount text. Students felt happy and enthusiast in learning recount text. Scrapbook helped the students to learn the material easily. Scrapbook can be one of visual media that is interesting especially for teaching writing recount text.